Contingency awareness as a prerequisite for differential contextual fear conditioning - Baeuchl, Christian; Hoppstädter, Michael; Meyer, Patric; Flor, Herta (Cognitive, affective, & behavioral neuroscience, 2019)
Contingency awareness during conditioning describes the phenomenon of becoming consciously aware of the association between a conditioned stimulus (CS) and an unconditioned stimulus (US). Despite the fact that contingency awareness is necessary for associative learning in some conditioning paradigms, its role in contextual fear conditioning, a variant that uses a context-CS (CTX) instead of a cue, has not been characterized thus far. We investigated if contingency awareness is a prerequisite for contextual fear conditioning and if subjects classified as aware differ from unaware subjects on a hemodynamic, autonomic, and behavioral level. We used a computer-generated picture context as CTX and slightly painful electric stimulation as US while we recorded brain responses by functional magnetic resonance imaging (fMRI), and obtained skin conductance responses (SCR) and verbal ratings of emotional valence and arousal. SCR analyses revealed that only aware subjects became conditioned to the US-associated CTX (CTX+). Brain activity related to the CTX+ was more strongly pronounced in fear-associated areas like the insula in the aware relative to the unaware group. Finally, the hippocampus was functionally connected to the cingulate cortex and posterior medial frontal gyrus in aware subjects relative to unaware subjects. These task-related differential connectivity patterns suggest that information exchange between the hippocampus and regions involved in the expression of conditioned fear and decision uncertainty is crucial for the acquisition of contingency knowledge. This study demonstrates the importance of contingency awareness for contextual fear conditioning and points to the hippocampus as a potential mediator for contingency learning in contextual learning.